Ferroptosis: A New Pathway in the Interaction between Gut Microbiota and Multiple Sclerosis - Junjie Jian; Jun Wei (Frontiers in Bioscience-Landmark)
Multiple sclerosis (MS) is a chronic autoimmune disorder marked by neuroinflammation, demyelination, and neuronal damage. Recent advancements highlight a novel interaction between iron-dependent cell death, known as ferroptosis, and gut microbiota, which may significantly influences the pathophysiology of MS. Ferroptosis, driven by lipid peroxidation and tightly linked to iron metabolism, is a pivotal contributor to the oxidative stress observed in MS. Concurrently, the gut microbiota, known to affect systemic immunity and neurological health, emerges as an important regulator of iron homeostasis and inflammatory responses, thereby influencing ferroptotic pathways. This review investigates how gut microbiota dysbiosis and ferroptosis impact MS, emphasizing their potential as therapeutic targets. Through an integrated examination of mechanistic pathways and clinical evidence, we discuss how targeting these interactions could lead to novel interventions that not only modulate disease progression but also offer personalized treatment strategies based on gut microbiota profiling. This synthesis aims at deepening insights into the microbial contributions to ferroptosis and their implications in MS, setting the stage for future research and therapeutic exploration.